2009
DOI: 10.1080/07448480903295367
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Firearm-Related Violence on College Campuses—Police Chiefs' Perceptions and Practices

Abstract: A greater awareness of the importance of a highly visible campus firearm policy and its potential for reducing firearm trauma on college campuses is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…Forty three percent had never collaborated with local EMS to discuss what to do in a school shooting scenario, and 22% did not have a plan for children with physical or learning disabilities (Graham et al., ). Similarly, the findings from more recent research on principals’ perceptions of firearm risks in high schools ( n = 349) highlighted that less than half of the schools represented in this sample had been trained with regard to how to respond to a school shooting (Price, Khubchandani, Payton, & Thompson, ; Thompson, Price, Mrdjenovich, & Khubchandani, ). Furthermore, the results of this work confirmed that many principals are unsure about what specific training and programs to implement as there is little evidence guiding existing school gun violence prevention practices (Price et al., ).…”
Section: Resultsmentioning
confidence: 77%
“…Forty three percent had never collaborated with local EMS to discuss what to do in a school shooting scenario, and 22% did not have a plan for children with physical or learning disabilities (Graham et al., ). Similarly, the findings from more recent research on principals’ perceptions of firearm risks in high schools ( n = 349) highlighted that less than half of the schools represented in this sample had been trained with regard to how to respond to a school shooting (Price, Khubchandani, Payton, & Thompson, ; Thompson, Price, Mrdjenovich, & Khubchandani, ). Furthermore, the results of this work confirmed that many principals are unsure about what specific training and programs to implement as there is little evidence guiding existing school gun violence prevention practices (Price et al., ).…”
Section: Resultsmentioning
confidence: 77%
“…Instead, weapons-carrying individuals were estimated to be 4.5 times more likely to be shot in an attack than were their counterparts who did not have a gun (Branas, Richmond, Culhane, Ten Have, & Wiebe, 2009). Additionally, most students, law enforcement personnel, and college administrators oppose provisions that allow concealed weapons on campus (Fallahi, Austad, Fallon, & Leishman, 2009;Thompson, Price, Mrdjenovich, & Khubchandani, 2009). The presence of lethal weapons on campuses could escalate the lethality of conflicts among students, provide students increased access to lethal means to commit suicide, contribute to more shooting accidents, increase the chance for police to mistake an armed student for an attacker, prevent some first responders (e.g., paramedics, fire fighters) from reaching victims if weapons are drawn, and increase collateral shootings among attackers and bystanders during attacks (Harnisch, 2008;Siebel, 2008).…”
Section: Concealed Weapons Permitsmentioning
confidence: 99%
“…While field findings show that 97% of campuses have a campus firearm policy (Thompson et al, 2009), that study did not address policy provision to a public campus communications portal, so this study's findings that 72% of institutions have posted a firearms policy on a Web-based portal may serve as an initial benchmark of Web-based public accessibility. Taken as a whole, provision of policy is similar for the research group (27% did not provide policy) and the control group (29% did not provide) of this study, which lends credence to field indications that campus carry policy is a national concern and less subject to regional impacts.…”
Section: Firearm Policymentioning
confidence: 99%
“…Attitudes towards issues related to campus carry may themselves reflect bias in that support groups for both sides of the issue have a strong correlation to race and gender (Benforado, 2010;Thompson et al, 2013), although studies may be compromised by a failure to accurately aggregate populations into subgroups that may demonstrate pockets of support within racial and ethnic groups (Johnson, 2013). Despite increasing public support for gun rights (Pew Research Center, 2016b) and a rise in the number of legal firearm sales in recent years (Federal Bureau of Investigation, 2014), student , faculty (Thompson et al, 2012), campus administrator (Price et al, 2014), and campus police (Thompson et al, 2009) support for concealed weapon campus carry policies is low. While student attitudes mirrored public attitudes up until approximately 2007 (Pew Research Center, 2016a), evidence is mounting that a rise in terrorism-related deaths (Global Terrorism Index, 2014), homicides by shootings (Centers for Disease Control, 2014), and high-profile mass shootings (Luca, Malhotra, & Poliquin, 2016) as well as the media's reporting of such events may have shifted public opinion in support of gun rights and policy support.…”
Section: Firearm Policymentioning
confidence: 99%